Testing Generative Thinking among Swazi Children - Mushoriwa, T.D.; Sibanda, J; Nkambule, H.Z. (EDUCARE, 2010)
ABSTRACT: This study tested and compared the generative thinking of second graders (7-8-year olds) and fifth graders (10-11-year olds) as a means to assess how generative thinking develops among children. Results from this study were compared with results obtained by Mushoriwa (2003) in a similar study in Zimbabwe in order to see if the development of generative thinking follows a similar pattern in different environments. Data were sourced from 40 second-graders and 40 fifth graders randomly selected from schools around Manzini. The survey research design was used, with interviews employed to collect the data. Crosstabs and a two-sample t-test were used to analyse the data. The study found no significant differences in generative thinking between second and fifth graders in the Swazi sample. In the comparative analyses, while significant differences in eye placements were observed between second graders in Swaziland and second graders in Zimbabwe, no significant differences in eye placements were observed between fifth graders in Swaziland and fifth graders in Zimbabwe. As for reasons/explanations for eye placements, significant differences between Swazi and Zimbabwean children were noted at both second grade and fifth grade levels. The study recommended the use, by teachers, of pedagogy that is promotive of generative thinking as well as the need for further research in the area focusing on environmental factors influencing the nature and developmental pattern of generative thinking. KEY WORDS: generative thinking, among children, comparative study, different environments, and Swazi children sample.About the Authors: T.D. Mushoriwa, Ph.D. is Senior Lecturer at the Department of Educational Foundations and Management UNISWA (University of Swaziland), Private Bag 4 Kwaluseni, Swaziland M201, Southern Africa; Mr. J. Sibanda is Lecturer at the Department of Primary Education UNISWA; and Ms. H.Z. Nkambule is Lecturer at the Department of Statistics and Demography UNISWA. One of them can be reached at: mushoriwa@yahoo.comÂ How to cite this article? Mushoriwa, T.D., J. Sibanda & H.Z. Nkambule. (2010). âTesting Generative Thinking among Swazi Childrenâ in EDUCARE: International Journal for Educational Studies, Vol.2(2) February, pp.197-210. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 4, 2009); Revised (January 14, 2010); and Published (February 17, 2010). Â